Characteristic study of fly-ash+quartz+illmenite composite coatings on copper substrates. Issue 1 (1st February 2013) - Mishra, Subash Chandra; Behera, Ajit
Abstract : Fly ash produced from iron and steel industries contains rich amount of metal oxides, which has the potential of using it as a coating material on structural and engineering components. This demand leads to the development and characterizes various types of composite coatings of fly ash by using a robust technique, that is, plasma spraying. Plasma spray technology has the advantage of being able to process various low-grade minerals to obtain value-added products and also to deposit metals, ceramics and a combination of these, generating approximately homogeneous coatings with the desired microstructure. In the present investigation, coatings are developed on copper substrates using fly-ash+quartz+illmenite composite at various plasma torch input power levels ranging from 11 to 21 kW DC. Metallographic and chemical characterization of the produced composite coatings was performed with the aid of scanning electron microscopy and X-ray diffraction analysis. The adhesion strength was measured by using coating pull-out method. Maximum adhesion strength is found to be 6·32 MPa. Here, adhesion strength was higher than that of fly-ash+quatz and fly-ash+illmenite composite coating. It was found that the quality and properties of the composite coating are significantly affected by the operating power level of the plasma spray torch. This study identifies fly ash+quartz+illmenite as a potential coating material for structural and engineering applications.